Pengaruh Penambahan Tepung Tapioka Terhadap Kualitas Dan Akseptabilitas Bakso Sapi - Salam N. Aritonang (Universitas Andalas, 2007)
The research was aimed to evaluate the effect of using cassava starch on the quality and acceptability of meatball. Six kilograms of ground beef meat which have been well mixed with spices of salt, garlic and pepper were divided into 5 sub-groups. Each sub-group of dough was mixed with 5 difrerent levels of cassava starch of 0 % (R0), 5 % (R1), 10 % (R2), 15 % (R3) and 20 % (R4), respectively. The dough were then made in small ball form (meatball) and subdivided into 4 sub-sub-groups as replications. The raw dough of meat ball was then cooked in boiling water for 15 minutes to produce ready to eat meatball products. The products were measured for pH, moisture and protein content, and acceptability. Results indicated that pH, moisture and protein content of the meatball were decreased significantly (P<0,01) by increasing the use of cassava starch. Acceptability of meatball by test consumers, however, was not significantly affected by the use of cassava starch. Therefore, cassava starch could be used up to 20 % in making meat ball.